Pembiasaan Nilai-Nilai Religius dalam Pendidikan Agama Islam di Madrasah Tsanawiyah Negeri 3 Bondowoso - Anwar, Khoirul; Saiful, Muhammad (Prodi Pendidikan Agama Islam IAINU Kebumen, 2024)
The habituation of religious values ​​in Islamic religious education is very urgent in the world of education, because through the habituation of Islamic religious education, students can know how to pray, fast, good manners and the signs in Islam. Habituation Religious education is integral in the child's world. Society is increasingly forgetting current religious and moral education. The large number of deviations illustrates that many people are increasingly putting aside morals. The existence of these deviations is the basis for researchers to study further regarding the habituation of religious values ​​in Islamic Religious Education at Madrasah Tsanawiyah Negeri 3 Bondowoso. The research focus in this case is (1) How to get used to religious values ​​in Islamic Religious Education at MTsN 3 Bondowoso, (2) What are the supporting and inhibiting factors for getting used to religious values ​​in Islamic Religious Education at MTsN 3 Bondowoso. This research uses a qualitative approach and a case study type of research. The research data collection was obtained from observations, interviews and documentation. This research uses data analysis methods, namely data condensation, data display, data presentation, and drawing conclusions, while testing the validity of the data uses technical triangulation and source triangulation. The results of the research concluded that: The habituation of religious values ​​in Islamic Religious Education at MTsN 3 Bondowoso includes: 1). Teacher's Example 2). Routine activities 3). Advice and religious values ​​developed at MTsN 3 Bondowoso are a) the value of worship, b) akhlakul karimah, c) discipline, d) example. The supporting and inhibiting factors for the habituation of religious values ​​in Islamic education at MTsN 3 Bondowoso, 1). Supporting factors: a) Principal policy b) Facilities (mushollah) c) Teacher's role, 2). Inhibiting factors: a) Lack of student awareness.